Automation of Recognizing Old Slavonic Manuscripts with help of Description Logics - Кучуганов, Александр Валерьевич Валерьевич; Касимов, Денис Рашидович Рашидович; Кучуганов, Валерий Никонорович Никонорович; Осколков, Павел Петрович Петрович (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]In the paper an approach to recognition of old Slavonic symbols is proposed, which includes the stages of ternary segmentation, detecting edges of areas, synthesis of two skeleton variants, forming a fuzzy graph, creating a logical description in a fuzzy description logic, and recognition with help of a subsystem of formal automatic reasoning. Results of preliminary experiments are provided, which confirm the perspective of the proposed approach.
Keywords: recognition, skeleton, structural elements, fuzzy graph, description logic, old printed texts, Old Church Slavonic language, Old Russian language